Survival Mechanisms of Campylobacter hepaticus Identified by Genomic Analysis and Comparative Transcriptomic Analysis of in vivo and in vitro Derived Bacteria - Van, Thi Thu Hao; Lacey, Jake A.; Vezina, Ben; Phung, Canh; Anwar, Arif; Scott, Peter C.; Moore, Robert J. (Frontiers in Microbiology, 2019)
Chickens infected with Campylobacter jejuni or Campylobacter coli are largely asymptomatic, however, infection with the closely related species, Campylobacter hepaticus, can result in Spotty Liver Disease (SLD). C. hepaticus has been detected in the liver, bile, small intestine and caecum of SLD affected chickens. The survival and colonisation mechanisms that C. hepaticus uses to colonise chickens remain unknown. In this study, we compared the genome sequences of fourteen newly sequenced Australian isolates of C. hepaticus, isolates from outbreaks in the United Kingdom, and reference strains of Campylobacter jejuni and Campylobacter coli, with the aim of identifying virulence genes associated with SLD. We also carried out global comparative transcriptomic analysis between C. hepaticus recovered from the bile of SLD infected chickens and C. hepaticus grown in vitro. This revealed how the bacteria adapt to proliferate in the challenging host environment in which they are found. Additionally, biochemical experiments confirmed some in silico metabolic predictions. We found that, unlike other Campylobacter sp., C. hepaticus encodes glucose and polyhydroxybutyrate metabolism pathways. This study demonstrated the metabolic plasticity of C. hepaticus, which may contribute to survival in the competitive, nutrient and energy-limited environment of the chicken. Transcriptomic analysis indicated that gene clusters associated with glucose utilisation, stress response, hydrogen metabolism, and sialic acid modification may play an important role in the pathogenicity of C. hepaticus. An understanding of the survival and virulence mechanisms that C. hepaticus uses will help to direct the development of effective intervention methods to protect birds from the debilitating effects of SLD.